API design for C++ - Reddy, Martin (Morgan Kaufmann, 2011)
The design of application programming interfaces can affect the behavior, capabilities, stability, and ease of use of end-user applications. With this book, you will learn how to design a good API for large-scale long-term projects. With extensive C++ code to illustrate each concept, API Design for C++ covers all of the strategies of world-class API development. Martin Reddy draws on over fifteen years of experience in the software industry to offer in-depth discussions of interface design, documentation, testing, and the advanced topics of scripting and plug-in extensibility. Throughout, he f.